2006
DOI: 10.1021/ol062151y
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Synthesis of 3-Heteroarylpropionic Acids

Abstract: A four component one-pot procedure (4-MC) was developed to assemble 3-heteroarylpropionic acids from commercially available materials. This new methodology affords the title compounds in high yields and without the use of chromatography. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 7 publications
0
28
0
2
Order By: Relevance
“…It is likely that thermal decomposition of the isoxazole 21 prevails in these conditions, showing its reactivity as a masked acetate. 31 Nucleophilic attack of the alcohol 1 on the C-5 carbon atom of the isoxazole ring and subsequent ring opening gave the acetate 22.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that thermal decomposition of the isoxazole 21 prevails in these conditions, showing its reactivity as a masked acetate. 31 Nucleophilic attack of the alcohol 1 on the C-5 carbon atom of the isoxazole ring and subsequent ring opening gave the acetate 22.…”
Section: Resultsmentioning
confidence: 99%
“…1). [1][2][3][4][5][6][7][8][9][10] Compounds 1 can be readily prepared from commercially available 3,5-dimethyl-4-nitro-isoxazole and aromatic aldehydes. 4 It has been shown that compounds 1 can be considered as cinnamate equivalents where the 4-nitro-isoxazole core can be hydrolyzed to give a carboxylate.…”
Section: Introductionmentioning
confidence: 99%
“…4 It has been shown that compounds 1 can be considered as cinnamate equivalents where the 4-nitro-isoxazole core can be hydrolyzed to give a carboxylate. 2,3,8,11 It is noteworthy that compounds 1 have enhanced reactivity compared to cinnamates due to the conjugation of the nitro group at position C-4 of the isoxazole core. Furthermore, compounds 1 have two electrophilic centers that can be selectively reacted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a part of our ongoing studies on the generation of chemical diversity using aromatic heterocycles, [7][8][9][10][11][12] we envisaged a novel synthesis of monobactams starting from commercially available 2-pyridones (Scheme 1). 2-Pyridones possess a low degree of aromaticity, and for this reason, they often have been employed as dienes in Diels-Alder reactions.…”
mentioning
confidence: 99%